PENGUASAAN KOSAKATA ANAK TUNARUNGU DALAM PEMBELAJARAN MEMBACA MELALUI PENERAPAN METODE MATERNAL - Hermanto, Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Mastery of vocabulary is one of the fundamental skills that are critical to the implementation of the communication process. Communication is both verbal communication or written communication or reading. Persons with hearing impairment to the condition causing the loss of auditory function process control upgrades vocabulary can not evolve naturally and result in limited communication capabilities. For that, the increase in vocabulary mastery for them must continue to be made and pursued in particular. One effort that can be done to improve the mastery of the vocabulary of children with hearing impairment through reading instructional with maternal reflective approach. There are two steps in reading instructional with maternal reflective method, that is ideo-visual reading, and receptive reading. But reading the receptive itself is divided into two phases, namely reading stage receptive vocabulary, and reading the receptive stage of the structure. Thus to improve the mastery of the vocabulary of children with hearing impairment through the maternal method, the ideo-visual literacy, and reading should be instilled early receptive. This instructional must be implemented correctly, systemic-systematic, programmed, and sustainable of all the teachers.